علاقة ثخانة قرص المفصل الفكي الصدغي مع النمو الوجهي حسب جاراباك لدى الأفراد الذكور البالغين (دراسة سيفالومترية وبالرنين المغناطيسي). - جحجاح يزن; حسن حازم حسن (Latakia University Journal -Medical Sciences Series, 2016)
Mandible articulates with the cranium via the TMJ. All the components of the TMJ, including the TMJ disc, seem to be associated with altered characteristics of the craniofacial complex and its growth. However, the exact role of the TMJ disc thickness during the process of the facial growth is not clear yet. Aim: The aim of this study is to investigate the association between the TMJ disc thickness and the facial growth determined according to Jarabak in adult male subjects with no clinical or MRI symptoms of Temporomandibular Joint Disorders. Materials and methods: 20 males from 19 to 25 years of age, were selected as volunteers from pretreatment patients undergoing orthodontic evaluation at the Department of Orthodontics and Dentofacial Orthopedics at Tishreen University with no clinical or MRI symptoms of TMDs. Studying cephalometric growth was performed according to Jarabak. MRI study was performed of both TMJ for calculating disk thickness. Pearson’s Correlation Coefficient was calculated to investigate the relationship between the TMJ disc thickness’s measurements (left &right) and cephalometric measurements determined according to Jarabak’s analysis for estimating facial growth. Results: There was significant relationship between the measurements of TMJ disc thickness (left &right) and the cephalometric measurements determined according to Jarabak for estimating facial growth in adult male subjects with no clinical or MRIsymptoms of TMDs. Conclusions : There was no relationship between the measurements of TMJ disc thickness (both sides) with the cephalometric measurements determined according to Jarabak for estimating facial growth in adult male subjects with no clinical or MRIsymptoms of TMDs. يتم فصل الفك السفلي مع الجمجمة بواسطة المفصل الفكي الصدغي، حيث ترتبط جميع مكونات المفصل الفكي الصدغي بما في ذلك القرص المفصلي مع الخصائص المتنوعة للمركب القحفي الوجهي ومع نموه، إلا إنه من غير الواضح بعد الدور الدقيق الذي تلعبه سماكة قرص المفصل الفكي الصدغي حلال علمية نمو الوجهي. هدف البحث:دراسة العلاقة بين ثخانة قرص المفصل الفكي الصدغي مع النمو الوجهي الذي تم تحديده حسب جاراباك وذلك لدى أفراد من الذكور البالغين ممن ليس لديهم أعراض سريرية لإضطرابات المفصل الفكي الصدغي ولا على صور الرنين المغناطيسي. مواد وطرق البحث: 20متطوع ذكر ممن لم يخضعوا لمعالجة تقويمية سابقة تم انتقاؤهم من المراجعين بهدف المعالجة التقويمية في قسم تقويم الأسنان والفكين بكلية طب الأسنان بجامعة تشرين تراوحت أعمارهم بين 19 و 25 سنة، المتطوعون المذكورون بدون أعراض سريرية لإضطرابات المفصل الفكي الصدغي ولا على صور الرنين المغناطيسي، لاحقاً تم إجراء دراسة سيفالومترية للنمو الوجهي وفق جاراباك، بالإضافة إلى دراسة صور المرنان للمفصل الفكي الصدغي بهدف قياس سماكة القرص المفصلي، تم إجراء تحليل معامل ارتباط بيرسون ما بين ثخانة قرص المفصل الفكي الصدغي (الأيمن والأيسر) مع القياسات السيفالومترية المحددة للنمو الوجهي حسب جاراباك. النتائج: لم نجد إرتباطاً ذو دلالة إحصائية مابين ثخانة قرص المفصل الفكي الصدغي (الأيمن والأيسر) مع القياسات السيفالومترية المحددة للنمو الوجهي حسب جاراباك لدى أفراد من الذكور البالغين ممن ليس لديهم أعراض سريرية لإضطرابات المفصل الفكي الصدغي ولا على صور الرنين المغناطيسي. الخلاصة: لا يوجد إرتباط ما بين مابين ثخانة قرص المفصل الفكي الصدغي (في كلا الجهتين) مع القياسات السيفالومترية المحددة للنمو الوجهي حسب جاراباك لدى أفراد من الذكور البالغين ممن ليس لديهم أعراض سريرية لإضطرابات المفصل الفكي الصدغي ولا على صور الرنين المغناطيسي.